EH Analysis Of Police Law That Deviates From The Ethical Perspective Of The Police Profession - Edi Saputra Hasibuan (International Asia Of Law and Money Laundering (IAML), 2023)
The development of Professional Ethics is contained in the regulation of the head of the profession and security section of the National Police. However, it is still a deviant act committed by members of the National Police. Like the cases we know such as sambo, tedi minahasa, akhirudin hasibuan where they are the police officers themselves who are supposed to set an example to the community but deviate from the essence of compliance and the basic duties of police members. The results of this study indicate that the deviation of the police apparatus is currently located by the person himself both in terms of economy and in terms of power so that the need for the implementation of the police ethics commission against members of the police who violate the law expressly without looking at the conditions of power carried out by members of the police.